Effect of Vibrations on Fracture Phenomena in Machining Aramid-Glass Fiber Hybrid Composites - E. Nakanishi; J. Suzuki; K. Isogimi (Engineering Transactions)
Machining of A-GFRP is needed to provide desired shapes, but involves many problems such as the drop of the surface integrity of the materials due to fluffing of the fibers. The ultrasonic vibration has been applied to the cutting tool during machining. The aramid-glass hybrid FRP consists of four layers of hybrid roving cloth and five layers of chopped strand glass mats, and a polyester resin as the matrix. This FRP has very poor machinability resulting from the presence of aramid fibers. The wear of the cutting tool and roughness of the machined surface are measured, and cutting phenomena are investigated by a comparison with normal cutting conditions.